Implementation of mobile health interventions in hypertension management and outcomes: A scoping review protocol - Saviour Edem Vidzro; Monica Ansu-Mensah; Siyabonga Dlamini; Desmond Kuupiel (PLoS ONE, 2026)
Background Hypertension remains a global health concern, significantly increasing the risk of cardiovascular disease, stroke, and mortality. Mobile health (mHealth) interventions are emerging as a promising solution for hypertension management, offering tools for remote monitoring, patient engagement, and data tracking. This scoping review aims to map the existing literature on mHealth interventions for hypertension, highlighting key trends, research gaps, and implications for clinical practice and future research. Objective This scoping review aims to map the breadth of literature on mHealth interventions for hypertension management, focusing on implementation (feasibility, acceptability, adoption), effectiveness, and health outcomes. Specifically, it seeks to identify the types of mHealth interventions used, implementation strategies across various settings, barriers and facilitators, and associated health outcomes. Methods This review will consist of a systematic literature search of databases such as PubMed, Scopus, Cochrane Library, Google Scholar, Web of Science, EBSCOhost, and EMBASE, augmented with grey literature, in accordance with the methodological framework developed by Arksey and O’Malley and improved by Levac et al. The study will be chosen using a two-phase screening procedure, and the Mixed Methods Appraisal Tool (MMAT) will be used to evaluate the study’s quality. Study characteristics, population information, intervention descriptions, results, and important findings will all be captured during data extraction. Results The review will identify the types of mHealth interventions, assess their effectiveness in blood pressure control, and evaluate key implementation outcomes, including feasibility, acceptability, and adoption as reflected by patient adherence, engagement, and satisfaction. Additionally, key research gaps will be highlighted, such as the need for long-term studies and diverse population representation. Conclusion This scoping review will provide a comprehensive overview of mHealth interventions for hypertension management, identifying effective strategies and highlighting areas for further research. The findings will inform healthcare providers, researchers, and policymakers on integrating mHealth technologies into hypertension care to improve patient outcomes.